Incidence of injuries among lacrosse athletes: a systematic review and meta-analysis. Issue 2 (4th March 2023) - Hasan, Laith K; Shelby, Tara; Bolia, Ioanna K; Chu, Timothy; Trasolini, Nicholas; Padilla, Francisco A; Levian, Brandon; Ihn, Hansel; Haratian, Aryan; Hatch, George F; Petrigliano, Frank A; Weber, Alexander E
ABSTRACT: Objectives: The purpose of this systematic review was to determine the incidence of injuries among lacrosse athletes and the differences in rates of injury by location and gender. Methods: The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were implemented to conduct this systematic review.[1] The following variables were extracted from each of the included articles: location of injury, gender of patient, and incidence of injury among study population. The methodological quality of the included studies was assessed using mixed-methods appraisal tool (MMAT) version 2018.[2] Estimated rates were reported as pooled proportion with 95% CI. Rates of injury were calculated as a rate per 1000 athletic exposures (AEs), defined as an athlete participating in 1 practice or competition in which he or she was exposed to the possibility of athletic injury. Results: This study found that the highest injury rate among lacrosse athletes was to the lower leg/ankle/foot with a rate of 0.66 injuries per 1000 AEs (95% CI, 0.51, 0.82). This injury pattern was also found to be the highest among both male and female lacrosse athletes. No statistical significance was detected when comparing rates of injury across gender, regardless of location. The injury pattern with the lowest rates of injury for female athletes being to the shoulder/clavicle and the neck for male athletes. Conclusion: The highest rate of injury among lacrosse athletes was to the lower leg/ankle/foot. As participation in lacrosse continues to rise, there is a greater need for understanding the rate of injury and injury characteristics for physicians and trainers to provide effective care to lacrosse athletes.